Efektivitas Kelas Ibu Hamil Dalam Peningkatan Pengetahuan Tentang Faktor Risiko Anemia Di Wilayah Kerja Puskesmas Wara Kota Palopo - Arnianti Arnianti; Dewi Hastuty; Yenni; Rosita; Yuniar Dwi Yanti; Jumriana Ibriani (Akademi Keperawatan Yarsi Samarinda, 2025)
Background: Anemia is the most common health problem in developing countries, including Indonesia. The purpose of this study was to determine the effectiveness of prenatal classes in preventing anemia at the Wara Community Health Center in Palopo City. Method: This type of research is a quasi-experimental study with a One Group Pretest Posttest Design approach. Before the intervention was given, respondents were given a pretest first and then continued with treatment with intensive prenatal class learning for 2 x in 1 month. After being given prenatal class learning, participants took a posttest. This study was conducted in the Wara Community Health Center Working Area in Palopo City. A total of 30 samples were selected using fixed exposure sampling, consisting of 30 pregnant women who attended the prenatal class. Knowledge data collection used interview techniques and questionnaire instruments. Bivariate analysis was carried out using a normality test to determine whether the data was normally distributed as a requirement to continue the Paired Sample T-test analysis with a probability value level (α) of 0.05 (95%). Results: After the intervention, 26 (87%) pregnant women had good knowledge, 2 (7%) had sufficient knowledge, and 2 (7%) pregnant women had low knowledge. The results of the paired sample T-test showed a significant influence of the class of pregnant women in increasing knowledge about anemia risk factors with a sig value (0.000 <0.05. Then there was a difference in the average value between the pretest and posttest with a Mean Paired Differences of -4.366 (8.4333-12.8000 = -4.366) and the difference in the difference was between -5.19575 to -3.53758 (95% (Confidence Interval of the Difference Lower and Upper).